2022
DOI: 10.3390/ijms23073550
|View full text |Cite
|
Sign up to set email alerts
|

Fascinating Molecular and Immune Escape Mechanisms in the Treatment of STIs (Syphilis, Gonorrhea, Chlamydia, and Herpes Simplex)

Abstract: The incidence of syphilis, gonorrhea, chlamydia, and herpes simplex has increased over the last decade, despite the numerous prevention strategies. Worldwide scientists report a surge in drug-resistant infections, particularly in immunocompromised patients. Antigenic variations in syphilis enable long-term infection, but benzathine penicillin G maintains its efficiency, whereas macrolides should be recommended with caution. Mupirocin and zoliflodacin were recently introduced as therapies against ceftriaxone-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 143 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…CT/HPV co-infection and the potential synergistic role of these infections in cervical carcinogenesis were highlighted previously [35,46,47,129,140,144,145]. CT GroEL, a marker of CT persistence has been associated with an increased risk of cervical cancer [143].…”
Section: Interaction Of Chlamydia Trachomatis With Human Papillomavir...mentioning
confidence: 86%
See 1 more Smart Citation
“…CT/HPV co-infection and the potential synergistic role of these infections in cervical carcinogenesis were highlighted previously [35,46,47,129,140,144,145]. CT GroEL, a marker of CT persistence has been associated with an increased risk of cervical cancer [143].…”
Section: Interaction Of Chlamydia Trachomatis With Human Papillomavir...mentioning
confidence: 86%
“…HSV is a double-stranded DNA virus from the family Herpesviridae that infects epithelial cells and neurons [ 145 ]. HSV-1 is transmitted by oral-to-oral contact and causes oral herpes, while HSV-2 is transmitted sexually and causes genital herpes.…”
Section: Co-infections Of Chlamydia Trachomatis An...mentioning
confidence: 99%
“…The transformation of RBs back into EBs occurs when the inclusion containing RBs reaches a critical volume and experiences nutrient and ATP depletion. The newly formed EBs are then released into the extracellular environment, initiating another round of infection (Scurtu et al, 2022). However, similar to mycoplasma, limited research has been conducted exploring the energy metabolism of chlamydia within the host cell.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Mestrovic et al have reported that azithromycin resistance, in vitro , could be raised through mutations in Ct 23S rRNA genes [ 79 ]. In addition, tetracycline resistance is developed by tet(M) gene mutations [ 80 ]. Benamri and colleagues described the fact that fluoroquinolones resistance could be developed via gyrA, parC, and ygeD gene mutations [ 81 ].…”
Section: Treatment Failure and Novel Approachesmentioning
confidence: 99%